The Concept of Mushtarak In The Translation Of The Quran (Contrarius Series: Law & Social Justice, 2026)
Mushtarak, an Arabic word, is defined as a word that has numerous meanings and definitions. Therefore, its presence in the Quran results in differences in the interpretation. Interpretations are acceptable as long as it can be understood through detailed explication. Occasionally, there are conflicting interpretations due to being manipulated arbitrarily by certain parties. This phenomenon of contradiction in interpretation is partly due to the concept of mushtarak found in the language. However, the concept of mushtarak is defined differently according to the field of knowledge. Therefore, this study hopes to identify the concept of mushtarak from various fields of knowledge and apply with mushtarak data from the religious text in the field of study of the Quran. The main objective is to ascertain the true concept of mushtarak which conforms to the content of the Quran. This is a qualitative study and uses the methodology of library research and text analysis. The findings show that both the field of tafsir and ulum al-Quran that adapt the concept of mushtarak is suitable to be applied to the study of the meaning of the Quran. Thus, any previous and modern usage of mushtarak term is deemed not important in this field as long as the concept of diversity of meaning exists. In the context of the translation of the Quran, any notion in meaning of a word must prioritize the terms and concepts contained in the field of tafsir and the science of the Quran in addition to taking into account other fields of knowledge that serve as a check and balance.